An antistatic and flame-retardant rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material and its preparation method and application
By using rutile titanium dioxide supported tin antimony oxide as a dopant in polystyrene composite materials, the problem of traditional materials being difficult to balance antistatic and flame retardancy is solved, efficient and environmentally friendly composite material preparation is achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202410389421.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-01
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-04-01
AI Technical Summary
While improving antistatic properties, traditional antistatic polystyrene composite materials have reduced flame retardant safety, making it difficult to take into account both antistatic and flame retardant properties.
Rutile titanium dioxide supported tin antimony oxide is used as a dopant, and by mixing with styrene monomer and other substances for modification and polymerization, an antistatic and flame retardant rutile titanium dioxide supported tin antimony oxide/expanded polystyrene composite material is prepared .
It achieves both antistatic and flame retardant properties of composite materials, while reducing production costs and environmental pollution. The process is simple and the doping amount is lower than traditional methods.
Smart Images

Figure CN118256042B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of expanded polystyrene composite materials, and in particular to an antistatic and flame-retardant rutile titanium dioxide-loaded antimony tin oxide / expanded polystyrene composite material and a preparation method and application thereof. Background Art
[0002] Expanded Polystyrene (EPS) refers to granules containing a foaming agent in a polystyrene matrix. Due to its excellent properties such as low thermal conductivity, low water absorption, sound insulation, moisture resistance, shock resistance, strong impact resistance and simple molding process, it is widely used as a heat insulation, smoke proof and earthquake-resistant material in the construction, shipbuilding, automobile, train, refrigeration and other industries. It is also widely used as a packaging material and has extremely broad application prospects.
[0003] Due to the trend of global economic transformation towards clean energy, the demand for EPS with single function is becoming saturated, and the demand for functional EPS is increasing, such as antistatic EPS, flame retardant EPS, super hydrophobic EPS, antibacterial EPS, colored EPS, toughened EPS, etc. In the foreseeable future, the position of functional EPS in the materials industry will become increasingly important.
[0004] Traditional antistatic polystyrene composite materials generally improve their conductivity by doping with conductive organic substances such as carbon black, carbon fiber, and polyaniline. These methods have complex manufacturing processes, high costs, severe environmental pollution, and high waste disposal costs. In addition, due to the doping with flammable organic substances, although the antistatic performance is improved, the flame retardant safety is further reduced, and it is impossible to take into account both antistatic and flame retardancy. Summary of the invention
[0005] In view of this, the object of the present invention is to provide an antistatic and flame retardant red titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material and its preparation method and application. The red titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material of the present invention has both antistatic and flame retardancy.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides an antistatic and flame-retardant rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material, comprising polystyrene foam and rutile TiO2 loaded antimony tin oxide doped in the polystyrene foam; the doping amount of rutile TiO2 loaded antimony tin oxide in the rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material is 0.5-2wt.% calculated based on the mass of styrene monomer.
[0008] Preferably, the doping amount of the rutile TiO2 loaded with antimony tin oxide is 1 to 1.5 wt.%.
[0009] Preferably, the mass proportion of tin element in the rutile TiO2-loaded tin antimony oxide is 20%, and the mass proportion of antimony element is 3-8%.
[0010] Preferably, the mass proportion of antimony element in the rutile TiO2-loaded antimony tin oxide is 5%.
[0011] The present invention also provides a method for preparing the rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material described in the above technical solution, comprising the following steps:
[0012] The rutile TiO2 loaded with antimony tin oxide, a silane coupling agent and an organic solvent are mixed and modified to obtain modified rutile TiO2@ATO;
[0013] The modified rutile TiO2@ATO, styrene monomer, initiator, dispersant, auxiliary dispersant and water are mixed to carry out polymerization reaction to obtain polystyrene particles doped with rutile TiO2@ATO;
[0014] The polystyrene particles doped with rutile TiO2@ATO are foamed to obtain the rutile titanium dioxide loaded antimony tin oxide / foamed polystyrene composite material.
[0015] Preferably, the mass ratio of the rutile TiO2-loaded antimony tin oxide to the silane coupling agent is 1:0.05-0.15.
[0016] Preferably, the mass ratio of the modified rutile TiO2@ATO, styrene monomer, initiator, dispersant and auxiliary dispersant is 0.1-0.4:20:0.5:0.14-0.35:0.303-0.7575.
[0017] Preferably, the initiator comprises dibenzoyl peroxide, the dispersant comprises hydroxyapatite, the auxiliary dispersant comprises sodium dodecylbenzene sulfonate and anhydrous sodium carbonate, and the mass ratio of the sodium dodecylbenzene sulfonate to anhydrous sodium carbonate is 0.01-0.025:1-2.5.
[0018] Preferably, the foaming temperature is 90-110° C. and the time is 6-12 hours.
[0019] The present invention also provides the use of the rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material described in the above technical scheme or the rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material prepared by the preparation method described in the above technical scheme in anti-static flame retardant thermal insulation and building thermal insulation materials.
[0020] The invention provides an antistatic and flame-retardant rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material, comprising polystyrene foam and rutile TiO2 loaded antimony tin oxide (rutile TiO2@ATO) doped in the polystyrene foam; the doping amount of rutile TiO2 loaded antimony tin oxide in the rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material is 0.5-2wt.% calculated on the basis of the mass of styrene monomer.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention adopts rutile TiO2@ATO as a dopant to give EPS unique properties, which not only makes the EPS composite material have antistatic and flame retardant properties, but also takes into account the antistatic and flame retardant functions. In addition, rutile TiO2@ATO is different from traditional organic doping, has less environmental pollution, low raw material prices, simple process, and lower doping amount than traditional organic doping, which further reduces production costs and the difficulty of handling reaction waste.
[0023] The data of the embodiment show that the surface resistance of the prepared rutile titanium dioxide supported antimony tin oxide / expanded polystyrene composite material is between 3.3×10 8 ~5.2×10 4 kΩ, and the limiting oxygen index is between 25.5% and 35.7%.
[0024] The present invention also provides a method for preparing the rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material described in the above technical solution, which has simple process, low equipment requirements, low raw material prices, low reaction waste treatment costs, and low environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a scanning electron microscope image of rutile TiO2@ATO prepared in Example 1;
[0026] Figure 2 This is a physical picture of the 0.5wt.% rutile TiO2@ATO-doped / expanded polystyrene composite material prepared in Example 3;
[0027] Figure 3 This is a physical picture of the 1wt.% rutile TiO2@ATO-doped / expanded polystyrene composite material prepared in Example 6;
[0028] Figure 4 This is a physical picture of the 2 wt.% rutile TiO2@ATO doped / expanded polystyrene composite material prepared in Example 8. DETAILED DESCRIPTION
[0029] The invention provides an antistatic and flame-retardant rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material, comprising polystyrene foam and rutile TiO2 loaded antimony tin oxide doped (physically doped) in the polystyrene foam; the doping amount of rutile TiO2 loaded antimony tin oxide in the rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material is 0.5-2wt.% calculated on the basis of the mass of styrene monomer.
[0030] In the present invention, the doping amount of the rutile TiO2 loaded with antimony tin oxide is preferably 1 to 1.5 wt.%.
[0031] In the present invention, the mass proportion of tin element in the rutile TiO2-loaded tin antimony oxide is preferably 20%, and the mass proportion of antimony element is preferably 3-8%, and more preferably 5%.
[0032] The present invention also provides a method for preparing the rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material described in the above technical solution, comprising the following steps:
[0033] The rutile TiO2 loaded with antimony tin oxide, a silane coupling agent and an organic solvent are mixed and modified to obtain modified rutile TiO2@ATO;
[0034] The modified rutile TiO2@ATO, styrene monomer, initiator, dispersant, auxiliary dispersant and water are mixed to carry out polymerization reaction to obtain small polystyrene particles doped with rutile TiO2@ATO;
[0035] The polystyrene particles doped with rutile TiO2@ATO are foamed to obtain the rutile titanium dioxide loaded antimony tin oxide / foamed polystyrene composite material.
[0036] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.
[0037] The invention mixes rutile TiO2 loaded with antimony tin oxide, a silane coupling agent and an organic solvent for modification to obtain modified rutile TiO2@ATO.
[0038] In the present invention, the rutile TiO2-loaded antimony tin oxide is preferably prepared by a method comprising the following steps:
[0039] One-dimensional rutile titanium dioxide, tin tetrachloride pentahydrate and antimony trichloride are mixed for chemical coprecipitation to obtain a mixture of rutile titanium dioxide, tin hydroxide and antimony hydroxide;
[0040] The mixture of the rutile titanium dioxide, tin hydroxide and antimony hydroxide is dried and calcined in sequence to obtain the rutile TiO2 loaded with tin antimony oxide.
[0041] The present invention has no special limitation on the source of the one-dimensional rutile titanium dioxide, and the titanium dioxide can be prepared by a source or a conventional preparation method known to those skilled in the art. In a specific embodiment of the present invention, the one-dimensional rutile titanium dioxide is preferably prepared by high-temperature calcination using metatitanic acid as a raw material.
[0042] In the present invention, the temperature of the chemical coprecipitation is preferably 60°C.
[0043] In the present invention, the calcination temperature is preferably 600° C., the calcination time is preferably 3 h, and the calcination is preferably performed in a muffle furnace.
[0044] In the present invention, the mass ratio of the rutile TiO2-loaded antimony tin oxide to the silane coupling agent is preferably 1:0.05-0.15, more preferably 1:0.1.
[0045] In the present invention, the silane coupling agent is preferably KH570 or KH550.
[0046] In the present invention, the organic solvent is preferably anhydrous ethanol.
[0047] In the present invention, the usage ratio of the rutile TiO2 loaded antimony tin oxide to anhydrous ethanol is preferably 1 g:20 mL.
[0048] In the present invention, the modification temperature is preferably 60°C and the modification time is preferably 6 hours. During the modification process, the hydrolysis functional groups of the silane coupling agent react with the hydroxyl groups on the surface of the rutile TiO2-loaded antimony tin oxide to impart lipophilicity and hydrophobicity to the material, thereby improving its dispersibility in polystyrene.
[0049] In the present invention, the modification preferably further includes drying.
[0050] In the present invention, the drying is preferably oven drying, the temperature of the oven drying is preferably 100° C., and the time is preferably 12 hours.
[0051] In a specific embodiment of the present invention, it is preferred to first put the rutile TiO2-loaded antimony tin oxide and anhydrous ethanol into a beaker, then add the silane coupling agent, and then place the beaker in a constant temperature water bath, maintain 60°C, and stir at 200rpm for 6 hours. After that, the obtained sample is centrifugally washed with anhydrous ethanol and placed in an oven at 100°C for 12 hours to obtain the modified rutile TiO2@ATO.
[0052] After obtaining the modified rutile TiO2@ATO, the present invention mixes the modified rutile TiO2@ATO, styrene monomer, initiator, dispersant, auxiliary dispersant and water to carry out polymerization reaction to obtain polystyrene particles doped with rutile TiO2@ATO.
[0053] In the present invention, the mass ratio of the modified rutile TiO2@ATO, styrene monomer, initiator, dispersant and auxiliary dispersant is preferably 0.1-0.4:20:0.5:0.14-0.35:0.303-0.7575, more preferably 0.1:20:0.5:0.14:0.303, 0.2:20:0.5:0.21:0.4545, 0.3:20:0.5:0.28:0.606 or 0.4:20:0.5:0.35:0.7575.
[0054] In the present invention, the initiator preferably includes dibenzoyl peroxide (BPO), the dispersant preferably includes hydroxyapatite, the auxiliary dispersant preferably includes sodium dodecylbenzene sulfonate (SDBS) and anhydrous sodium carbonate, and the mass ratio of sodium dodecylbenzene sulfonate to anhydrous sodium carbonate is preferably 0.01-0.025:1-2.5, more preferably 0.1:1; the dibenzoyl peroxide is an initiator, which decomposes at 90°C to initiate styrene polymerization, and the role of the hydroxyapatite, sodium dodecylbenzene sulfonate and anhydrous sodium carbonate is to ensure that the styrene and water system forms uniform water-in-oil particles under stirring, thereby forming polystyrene microspheres.
[0055] In the present invention, the mass ratio of the modified rutile TiO2@ATO to water is preferably 0.1-0.4 g:60 mL, and more preferably 0.2-0.3 g:60 mL.
[0056] In the present invention, the polymerization reaction preferably includes the following process: maintaining the temperature at 50°C for 1 hour, then increasing the temperature stepwise to 90-92°C at a rate of 10-15°C per 30 minutes, and maintaining for 2.5 hours.
[0057] In the present invention, the polymerization reaction is preferably carried out in a constant temperature water bath with stirring, and the stirring speed is preferably 360 rpm.
[0058] In the present invention, the styrene monomer, initiator, dispersant, auxiliary dispersant and water are preferably added to the modified rutile TiO2@ATO at the same time.
[0059] In the present invention, after the polymerization reaction is completed, the obtained solid particles all harden and sink. The present invention preferably closes the reaction and then cools naturally to room temperature, washes repeatedly with deionized water three times, and then puts into an oven at 60° C. and dries for 12 hours to obtain the polystyrene particles doped with rutile TiO2@ATO.
[0060] In the present invention, the particle size of the polystyrene particles doped with rutile TiO2@ATO is preferably 1.6 to 2 mm.
[0061] After obtaining the polystyrene small particles doped with rutile TiO2@ATO, the present invention foams the polystyrene particles doped with rutile TiO2@ATO to obtain the rutile titanium dioxide loaded antimony tin oxide / foamed polystyrene composite material.
[0062] In the present invention, the foaming temperature is preferably 90 to 110° C., and the foaming time is preferably 6 to 12 hours.
[0063] In the present invention, the foaming preferably includes the following steps: soaking the polystyrene particles doped with rutile TiO2@ATO in deionized water for 8 to 10 hours, placing the granular material (10 g) into a reactor after the soaking is completed, adding deionized water (100 mL) into the reactor and then closing the reactor, introducing CO2 gas into the reactor at room temperature, and when the pressure in the reactor reaches 4.5 MPa, stopping ventilation and starting to slowly heat up at a rate of 10 to 15°C per 10 minutes, and maintaining the temperature for 6 hours after reaching 90 to 110°C, and then quickly discharging the CO2 gas in the reactor within 10 to 20 seconds, then opening the reactor, and naturally cooling to room temperature to obtain the rutile titanium dioxide loaded antimony tin oxide / foamed polystyrene composite material.
[0064] The present invention also provides the use of the rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material described in the above technical scheme or the rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material prepared by the preparation method described in the above technical scheme in anti-static flame retardant thermal insulation and building thermal insulation materials.
[0065] The present invention has no particular limitation on the specific manner of the application, and any manner familiar to those skilled in the art may be used.
[0066] In the present invention, the application is preferably used for instrument and electrical protection or chemical equipment.
[0067] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0068] Example 1
[0069] One-dimensional rutile titanium dioxide was synthesized by high-temperature calcination using metatitanic acid as raw material. A mixture of rutile titanium dioxide, tin hydroxide and antimony hydroxide was synthesized by chemical coprecipitation at a water bath temperature of 60°C using the prepared one-dimensional rutile titanium dioxide, tin tetrachloride pentahydrate and antimony trichloride. The mixture was filtered, washed and dried, and then calcined in a muffle furnace at 600°C for 3h to obtain one-dimensional rutile titanium dioxide loaded with tin antimony oxide. The mass proportion of tin element in the prepared rutile TiO2@ATO is 20%, and the mass proportion of antimony element is 5%. The scanning electron microscope image of the obtained product rutile TiO2@ATO is shown in Figure 1 .
[0070] 3g of rutile TiO2@ATO and 60mL of anhydrous ethanol were placed in a beaker, and 0.15g of silane coupling agent KH570 was added at the same time. The beaker was placed in a constant temperature water bath, maintained at 60°C, and stirred at 200rpm for 6h. After that, the obtained sample was centrifugally washed with anhydrous ethanol, and then placed in an oven at 100°C for 12h to obtain the modified rutile TiO2@ATO after the sample was dried. 0.1g of modified rutile TiO2@ATO was added to a three-necked flask, and 20g of styrene monomer, 60mL of deionized water, 0.5g of dibenzoyl peroxide, 0.003g of sodium dodecylbenzene sulfonate, 0.3g of anhydrous sodium carbonate and 0.14g of hydroxyapatite were added at the same time. The three-necked flask was placed in a constant temperature water bath, and the stirring speed was adjusted to 360rpm. The temperature was kept at 50℃ for 1h, and then the temperature was increased to 90℃ at a rate of 10℃ every 30min, and kept for 2.5h until all the polystyrene beads hardened and sank. After the reaction was closed, it was naturally cooled to room temperature, washed repeatedly with deionized water three times, and then placed in an oven at 60℃ for 12h to obtain polystyrene particles doped with rutile TiO2@ATO with a doping amount of 0.5wt.% (calculated by the mass of styrene monomer). After measurement, the particle size of the obtained polystyrene particles was 1.6-2mm.
[0071] Take 10g of polystyrene particles doped with rutile TiO2@ATO and soak them in deionized water for 8h. After soaking, put the small balls into a reactor, add 100mL of deionized water into the reactor, close the reactor, and introduce CO2 gas into the reactor at room temperature. When the pressure in the reactor reaches 4.5MPa, stop ventilation and start to slowly heat up at a rate of 10℃ every 10min. After reaching 90℃, keep it for 6h. After keeping the temperature for 6h, quickly discharge the CO2 gas in the reactor within 10s, then open the reactor, and naturally cool it down to room temperature to obtain a rutile titanium dioxide-doped antimony tin oxide / expanded polystyrene composite material with a doping amount of 0.5wt.%.
[0072] Example 2
[0073] Same as Example 1, except that the amount of silane coupling agent KH570 was changed to 0.3 g.
[0074] Example 3
[0075] Same as Example 1, only the silane coupling agent KH570 was changed to 0.45g. The prepared composite material of doped rutile titanium dioxide loaded with antimony tin oxide / expanded polystyrene with a doping amount of 0.5wt.% is shown in the actual picture. Figure 2 .
[0076] Example 4
[0077] The same as Example 3, except that the mass proportion of antimony element in rutile TiO2@ATO is changed to 3%.
[0078] Example 5
[0079] The same as Example 3, except that the mass proportion of antimony element in rutile TiO2@ATO is changed to 8%.
[0080] Example 6
[0081] 3 g of rutile TiO2@ATO prepared in Example 1 and 60 mL of anhydrous ethanol were placed in a beaker, and 0.45 g of silane coupling agent KH570 was added at the same time. The beaker was placed in a constant temperature water bath, maintained at 60°C, and stirred at 200 rpm for 6 hours. After that, the obtained sample was centrifugally washed with anhydrous ethanol, and then placed in an oven at 100°C for 12 hours to obtain the modified rutile TiO2@ATO after the sample was dried. 0.2g of modified rutile TiO2@ATO was added to a three-necked flask, and 20g of styrene monomer, 60mL of deionized water, 0.5g of dibenzoyl peroxide, 0.0045g of sodium dodecylbenzene sulfonate, 0.45g of anhydrous sodium carbonate and 0.21g of hydroxyapatite were added at the same time. The three-necked flask was placed in a constant temperature water bath, and the stirring speed was adjusted to 360rpm. The temperature was kept at 50℃ for 1h, and then the temperature was increased to 90℃ at a rate of 10℃ every 30min, and kept for 2.5h until all the polystyrene beads hardened and sank. After the reaction was closed, it was naturally cooled to room temperature, washed repeatedly with deionized water three times, and then placed in an oven at 60℃ for 12h to obtain polystyrene particles doped with rutile TiO2@ATO with a doping amount of 1wt.% (calculated by the mass of styrene monomer). After measurement, the particle size of the obtained polystyrene particles was 1.6-2mm.
[0082] Take 10g of polystyrene particles doped with rutile TiO2@ATO and soak them in deionized water for 8h. After soaking, put the small balls into a reactor, add 100mL of deionized water into the reactor and close the reactor. Pass CO2 gas into the reactor at room temperature. When the pressure in the reactor reaches 4.5MPa, stop ventilation and start to slowly heat up at a rate of 10°C every 10min. After reaching 90°C, keep it for 6h. After maintaining the temperature for 6h, quickly discharge the CO2 gas in the reactor within 10s, then open the reactor and naturally cool it to room temperature to obtain a rutile titanium dioxide doped with antimony tin oxide / expanded polystyrene composite material with a doping amount of 1wt.%. See the actual picture of the prepared rutile titanium dioxide doped with antimony tin oxide / expanded polystyrene composite material with a doping amount of 1wt.%. Figure 3 .
[0083] Example 7
[0084] The same as Example 6, except that the modified rutile TiO2@ATO powder is 0.3 g, sodium dodecylbenzene sulfonate is 0.006 g, anhydrous sodium carbonate is 0.6 g, and hydroxyapatite is 0.28 g.
[0085] Example 8
[0086] Same as Example 6, only the modified rutile TiO2@ATO powder is 0.4g, sodium dodecylbenzene sulfonate is 0.0075g, anhydrous sodium carbonate is 0.75g, and hydroxyapatite is 0.35g. The prepared rutile titanium dioxide doped with 2wt.% antimony tin oxide / foamed polystyrene composite material (calculated by styrene monomer mass) is shown in the actual picture. Figure 4 .
[0087] Example 9
[0088] Same as Example 8, except that the foaming temperature was changed to 100°C.
[0089] Example 10
[0090] Same as Example 8, except that the foaming temperature was changed to 110°C.
[0091] The performance of the rutile titanium dioxide-doped antimony tin oxide-loaded / expanded polystyrene composite materials obtained in Examples 1 to 10 was investigated respectively, and the specific method is as follows:
[0092] 1. Antistatic performance
[0093] The prepared rutile titanium dioxide-doped antimony tin oxide-loaded / expanded polystyrene composite material was cut into square sheets with a side length of 10 mm and a thickness of 0.5 mm using a blade, and then the volume resistivity of the sheet was measured using an ST2648 ultra-high resistance micro-current tester.
[0094] 2. Flame retardancy
[0095] Refer to ASTM D2863 to test the limiting oxygen index.
[0096] The limiting oxygen index of the combustion process of the rutile titanium dioxide-doped antimony tin oxide-loaded / expanded polystyrene composite material was obtained by testing with an oxygen index tester.
[0097] The surface resistance of pure polystyrene foam was measured to be 9.8×10 10 kΩ, and the limiting oxygen index is 18%.
[0098] Table 1 shows the preparation parameters and performance test results of Examples 1 to 10.
[0099] Table 1 Preparation parameters and performance test results of Examples 1 to 10
[0100]
[0101]
[0102] As shown in Table 1, the surface modification of rutile TiO2@ATO by using silane coupling agent KH550 can significantly improve the doping effect. When the doping amount reaches 2wt.% of the mass of styrene monomer, the surface resistance of the rutile titanium dioxide-loaded antimony tin oxide / foamed polystyrene composite material is reduced to 5.0×10 4 kΩ, reaching the antistatic performance requirements, and with the gradual increase of foaming temperature, the flame retardant properties of the composite material gradually increased. At a foaming temperature of 110°C, the limiting oxygen index was 35.7%, which was significantly improved compared to pure polystyrene foam.
[0103] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. An antistatic and flame retardant rutile titanium dioxide-loaded antimony tin oxide / expanded polystyrene composite material, characterized in that: The invention comprises polystyrene foam and rutile TiO2-loaded antimony tin oxide doped in the polystyrene foam; the doping amount of rutile TiO2-loaded antimony tin oxide in the rutile titanium dioxide-loaded antimony tin oxide / foamed polystyrene composite material is 0.5-2wt.% calculated based on the mass of styrene monomer; The mass proportion of tin element in the rutile TiO2-loaded tin antimony oxide is 20%, and the mass proportion of antimony element is 3-8%; The preparation method of the rutile titanium dioxide loaded antimony tin oxide / foamed polystyrene composite material comprises the following steps: The rutile TiO2 loaded with antimony tin oxide, a silane coupling agent and an organic solvent are mixed for modification to obtain modified rutile TiO2@ATO; the modified rutile TiO2@ATO, a styrene monomer, an initiator, a dispersant, an auxiliary dispersant and water are mixed for polymerization reaction to obtain polystyrene particles doped with rutile TiO2@ATO; The polystyrene particles doped with rutile TiO2@ATO are foamed to obtain the rutile titanium dioxide loaded antimony tin oxide / foamed polystyrene composite material.
2. The rutile titanium dioxide-loaded antimony tin oxide / expanded polystyrene composite material according to claim 1, characterized in that: The doping amount of the rutile TiO2 loaded with antimony tin oxide is 1 to 1.5 wt.%.
3. The rutile titanium dioxide supported antimony tin oxide / expanded polystyrene composite material according to claim 1, characterized in that: The mass proportion of antimony element in the rutile TiO2 loaded antimony tin oxide is 5%.
4. The method for preparing the rutile titanium dioxide supported antimony tin oxide / expanded polystyrene composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The rutile TiO2 loaded with antimony tin oxide, a silane coupling agent and an organic solvent are mixed for modification to obtain modified rutile TiO2@ATO; the modified rutile TiO2@ATO, a styrene monomer, an initiator, a dispersant, an auxiliary dispersant and water are mixed for polymerization reaction to obtain polystyrene particles doped with rutile TiO2@ATO; The polystyrene particles doped with rutile TiO2@ATO are foamed to obtain the rutile titanium dioxide loaded antimony tin oxide / foamed polystyrene composite material.
5. The preparation method according to claim 4, characterized in that: The mass ratio of the rutile TiO2 loaded antimony tin oxide to the silane coupling agent is 1:0.05-0.
15.
6. The preparation method according to claim 4, characterized in that: The mass ratio of the modified rutile TiO2@ATO, styrene monomer, initiator, dispersant and auxiliary dispersant is 0.1-0.4:20:0.5:0.14-0.35:0.303-0.7575.
7. The preparation method according to claim 6, characterized in that: The initiator comprises dibenzoyl peroxide, the dispersant comprises hydroxyapatite, the auxiliary dispersant comprises sodium dodecylbenzene sulfonate and anhydrous sodium carbonate, and the mass ratio of the sodium dodecylbenzene sulfonate to the anhydrous sodium carbonate is 0.01-0.025:1-2.
5.
8. The preparation method according to claim 4, characterized in that: The foaming temperature is 90-110° C. and the foaming time is 6-12 hours.
9. Use of the rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material according to any one of claims 1 to 3 or the rutile titanium dioxide loaded antimony tin oxide / expanded polystyrene composite material prepared by the preparation method according to any one of claims 4 to 8 in antistatic flame retardant thermal insulation and building thermal insulation materials.
Citation Information
Patent Citations
Styrene resin foamable particle, foaming particle, foamed molding and heat insulation material for living space
JP2016188325A